A cause of oversupply and failure in the shipping market: measuring herding behavior effects. Issue 8 (17th November 2018) - Lee, Taylor Tae-Hwee; Yip, Tsz Leung
ABSTRACT: The shipping market is volatile. In general, the shipping market cycle shows four stages, through—recovery—peak—collapse, while a upward trend lasts for 7~8 years and a downward trend for another 7~8 years. So the market's bubble is not sustainable but always ends in a recessionary trend. The economic cycle is common knowledge and an axiom of the shipping industry, but many ship-owners take no account of it. Previous study stated that ship-owners' fears, triggered by a violently changeable market, make them mimic the crowd mind or herd mentality, following market sentiment. This study aims to measure the effects of herding behavior (HB), triggered by market sentiment, on the shipping market. We attempt to address two research questions: (1) How does HB arise, and what course does it follow? (2) How many vessels (or how many tons) were purchased under the influence of HB? We estimate that 50.5% (227.8 vessels) of the total vessels or 30.4% (3, 670.2 tons) of the total tonnage were purchased under the influence of HB. Looking at international finance, we found that ship investment HB is a very strong factor of the recent shipping market, at least in Korea.